Effects of periodontal therapy with topical antibiotics in the glycemic control of diabetic patients: systematic review. - Aranzazu-Moya, Gloria Cristina (Revista Estomatología, 2019)
Background: Periodontal disease is considered as a diabetes complication and has been suggested that periodontal treatment plus antibiotics should reduce glycated hemoglobin A, by reducing local production of pro inflammatory substances.Objective: To evaluate diabetic patients with periodontal disease under periodontal treatment plus topical antibiotics and reduction of  HbA1c, compared to diabetic patients under periodontal treatment without antibiotics.Materials and Methods: Using PUBMED, SCOPUS, WEB OF SCIENCE, EMBASE and Google Scholar data bases, were screened documents from 2008 to 2018. The documents included were the clinical studies, which included non-surgical periodontal treatment plus topical antibiotics, whose outcomes included the HbA1c report. Two independent researchers evaluate title; abstract and bias risk with Downs Black scale and Cochrane tool. Documents with a score higher than 15 on average by the two evaluators were included.Results: Five articles, which find inclusion criteria, were identified. Two documents failed to demonstrate statistically significant effect when compared to non-surgical periodontal therapy alone.Conclusion: In general a modest reduction of HbA1c was identified when using antibiotic therapy.